PI and LQR controllers for Frequency Regulation including Wind Generation - Semaria Ruiz; Julian Patiño; Jairo Espinosa (Institute of Advanced Engineering and Science, 2018)
The increasing use of renewable technologies such as wind turbines in power systems may require the contribution of these new sources into grid ancillary services, such as Load Frequency Control. Hence, this work dealt with the performance comparison of two traditional control structures, PI and LQR, for secondary regulation of Load Frequency Control with the participation of variable-speed wind turbines. For this purpose, the doubly-fed induction generator wind turbine was modeled with additional control loops for emulation of the inertial response of conventional machines for frequency regulation tasks. Performance of proposed strategies was verified through simulation in a benchmark adapted from the WSCC 3 machines 9-bus test system. Results showed overall superior performance for LQR controller, although requiring more strenuous control effort from conventional units than PI control.